The Effect Of Motivation and Work Discipline On Job Satisfaction with Compensation as an Intervening Variable in BPJS Ketenagakerjaan West Sumatra Region - Danil Ramdani; Kiki Farida Ferine; M. Isa Indrawan (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to examine the effect of motivation and work discipline on job satisfaction with compensation as an intervening variable at BPJS Ketenagakerjaan West Sumatra Region.. This research employs a quantitative approach using a survey method. The research sample consists of 109 employees selected through a saturated sampling technique. Data were collected using questionnaires and analyzed using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. The results indicate that motivation and work discipline have a positive and significant effect on job satisfaction. Furthermore, motivation and work discipline also have a positive and significant effect on compensation. Compensation has a positive and significant effect on job satisfaction and is proven to mediate the relationship between motivation, work discipline, and job satisfaction. Therefore, improving employee motivation and work discipline supported by a fair and appropriate compensation system can enhance job satisfaction among employees of BPJS Ketenagakerjaan Solok.